PENGOLAHAN LIMBAH CAIR DOMESTIK METODE BIOFILTER AEROB - Mualim; Agus Widada; Krisdiyanta (Universitas Adiwangsa Jambi, 2022)
Abstract: Domestic wastewater can be divided into wastewater and wastewater. This is exacerbated by not all communities having a wastewater treatment plant beforehand. This study aims to determine the quality of the parameters TSS, BOD5, oil and fat in domestic wastewater after treatment with the aerobic biofilter method. The type of research used is True Experiment Design with a research design of Pretest-Posttest Control Group Design. The population in this study is domestic liquid waste. The sample is 490 liters. The tool used in this research is a series of tools in the form of an aerobic biofilter. Data analysis was carried out by Paired T-Test. The results of measuring the quality of domestic liquid waste compared to the Regulation of the Minister of Environment and Forestry Number 68 of 2016 show that the difference in BOD5 levels between pre and control is 14.64 with a standard deviation of 0.35 and the difference between pre and post tests is 18.1 with a standard deviation of 0.36. The results of the statistical test obtained a value of <.001 which means that there is a significant difference because the p-value is <0.05. The difference in TSS levels between pre and control was 35.94 with a standard deviation of 1.84 and the difference between pre and post test was 39.5 with a standard deviation of 1.80. The results of the statistical test obtained a value of <.001 which means that there is a significant difference because the p-value is <0.05. It can be seen that the difference in oil and fat content between pre and control was 1.67 with a standard deviation of 0.55 and the difference between the pre and post test was 3.4 with a standard deviation of 1.05. The statistical test results obtained a value of 0.035 which means that there is a significant difference because the p-value <0.05.It is hoped that the public can pay attention to the domestic liquid waste that comes out of their respective housing, there should be liquid waste treatment.